2003
DOI: 10.1095/biolreprod.102.009340
|View full text |Cite
|
Sign up to set email alerts
|

The Making of “Transgenic Spermatozoa”1

Abstract: The processes of making transgenic animals by microinjecting DNA into the pronucleus of a fertilized oocyte or after the transfection of embryonic stem cells are now well established. However, attempts have also been made, with varying degrees of success, to use spermatozoa as a vector for transgenesis in mammals and other vertebrates during the last decade. A number of different approaches for making transgenic spermatozoa have been developed. These include directly incubating mature, isolated spermatozoa wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
2
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 75 publications
3
27
2
4
Order By: Relevance
“…Nevertheless this technique has a limited capability to incorporate the DNA into the host genome. In order to improve the DNA incorporation it is possible to expose the sperm to electrical field (electroporation), which has brought good results in cattle (Rieth et al 2000;Celebi et al 2003). …”
Section: State Of the Artmentioning
confidence: 99%
“…Nevertheless this technique has a limited capability to incorporate the DNA into the host genome. In order to improve the DNA incorporation it is possible to expose the sperm to electrical field (electroporation), which has brought good results in cattle (Rieth et al 2000;Celebi et al 2003). …”
Section: State Of the Artmentioning
confidence: 99%
“…Sperm-mediated transgenesis involves different approaches: in vitro sperm-DNA incubation followed by in vitro fertilization or intracytoplasmic sperm injection (ICSI), and in vivo or in vitro germline gene transfer (Celebi et al, 2003).…”
Section: C) Sperm-mediated Transgenesismentioning
confidence: 99%
“…In the last years, we have been interested to define the molecular mechanisms underlying sperm-mediated gene transfer for the generation of transgenic animals using sperm cells (see reviews by Spadafora, 1998;Chan et al, 2000;Celebi et al, 2003). In the course of our studies to characterize the mechanism of interaction between sperm cells and exogenous DNA molecules, we have found that these cells are endowed with an unexpected network of metabolic functions that are normally silent, yet are activated at fertilization (Spadafora, 1998).…”
Section: Endogenous Rt Activity Is Required For Mouse Early Embryonicmentioning
confidence: 99%